Work Posture Analysis Using Work Safe Office Ergonomics and Musculoskeletal Disorders (MSDs) in Teachers - Indri Seta Septadina; Wardiansah; Agita Diora Fitri; Muzhaffar Zaid Rahman; Richard D Naibaho (Poltekkes Kemenkes Surabaya, 2025)
Background: Teachers are required to maintain prolonged sitting postures while engaging in complex and demanding tasks, placing them at increased risk for work-related musculoskeletal disorders (MSDs). Ergonomics plays a critical role in minimizing these risks, yet its importance is often underrecognized in the teaching profession. Moreover, in Indonesia, studies using direct observation methods such as the WorkSafe Ergonomics Tool remain limited. This study aims to analyse the relationship between work posture, assessed using the WorkSafe Ergonomic Office Tool, and musculoskeletal disorders among high school teachers. Methods: This study is an observational analytical study with a cross-sectional design on 55 Islamic Senior High School 3 teachers in Palembang City, who met the inclusion and exclusion criteria obtained using the total sampling technique. Data were obtained by filling out questionnaires and observing the work postures of teachers using the Ergonomic Office instrument by WorkSafe. Meanwhile, the musculoskeletal pain indicator uses the Numeric Rating Scale (NRS). Data were analyzed using the Chi-Square test. Results: The study results showed that most inappropriate work postures were found in the back in 78,2% of teachers and were significantly associated with pain in the head (p=0.033; OR=3.6) and back (p=0.046; OR=0.210). Conclusion: These findings highlight the urgent need for ergonomic adjustments in educational environments. Utilising approved observational instruments, such as the WorkSafe Ergonomic Office Tool, can improve early identification and preventative measures for musculoskeletal problems among teachers in Indonesia.